(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Financial stress has become an increasingly important concern among graduate students due to rising educational costs, increasing living expenses, limited financial resources, and uncertainty regarding future employment opportunities. While previous studies have examined financial literacy, financial self-efficacy, and financial well-being separately, limited research has integrated these constructs within a single conceptual framework, particularly in the context of emerging educational regions of India. This study addresses this research gap by developing an integrated conceptual understanding of the relationships among financial literacy, financial self-efficacy, financial resilience, financial stress, and financial well-being. The study adopts a conceptual and descriptive research design based on a systematic review of secondary literature collected from peer-reviewed journal articles, books, academic reports, and scholarly publications. The review indicates that financial literacy and financial self-efficacy significantly influence financial behaviour, budgeting practices, financial decision-making, and students’ ability to cope with financial stress. Educational expenses, accommodation costs, educational debt, family financial responsibilities, and socioeconomic vulnerability are identified as major contributors to financial stress among graduate students. Students with higher financial knowledge and stronger financial confidence are generally better able to maintain financial stability and adapt to financial challenges. The study highlights the importance of financial education initiatives, counselling support, and institutional interventions in improving financial resilience and overall financial well-being. The novelty of this study lies in proposing an integrated conceptual framework that links financial literacy, financial self-efficacy, financial resilience, financial stress, and financial well-being, providing a foundation for future empirical research in emerging educational regions of India.